Fitness costs of resistance to insecticides in insects - Gul, Hina; Gadratagi, Basana Gowda; Güncan, Ali; Tyagi, Saniya; Ullah, Farman; Desneux, Nicolas; Liu, Xiaoxia (Frontiers in Physiology, 2023)
The chemical application is considered one of the most crucial methods for controlling insect pests, especially in intensive farming practices. Owing to the chemical application, insect pests are exposed to toxic chemical insecticides along with other stress factors in the environment. Insects require energy and resources for survival and adaptation to cope with these conditions. Also, insects use behavioral, physiological, and genetic mechanisms to combat stressors, like new environments, which may include chemicals insecticides. Sometimes, the continuous selection pressure of insecticides is metabolically costly, which leads to resistance development through constitutive up-regulation of detoxification genes and/or target-site mutations. These actions are costly and can potentially affect the biological traits, including development and reproduction parameters and other key variables that ultimately affect the overall fitness of insects. This review synthesizes published in-depth information on fitness costs induced by insecticide resistance in insect pests in the past decade. It thereby highlights the insecticides resistant to insect populations that might help design integrated pest management (IPM) programs for controlling the spread of resistant populations.